Pelatihan Pembelajaran di Era Vuca pada Guru SMP dan SMK Insan Nur Muhammad Desa Tapos I Kecamatan Tenjolaya Kabupaten Bogor - Zainal Abidin; Muhamad Riyad; Budi Panca (LPPM Institut Nasional Laa Roiba Bogor, 2022)
The reality that is happening in the world globally today is experiencing turbulence, so the impact is that many things are changing rapidly (volatality), uncertainty (uncertainty), complex (complexity) and often confusing (ambiguity). Today we see the emergence of strange phenomena that we never imagined would be present before, namely changes that are visible and very significant affect the way of life and the mindset of humans as a whole. The current global education world is facing the so-called technology and information gap between digital immigrants (old teachers who learn technology) and digital natives (students who enjoy and use technology), while there are still teachers who are currently quite stuttering in dealing with students or students who speak technology. These old teachers often find it difficult to change the teaching and learning paradigm, find it difficult to adjust to the latest trends in teaching and digital-based learning media that are developing fast, feel threatened by technology, and feel confused to change. Ideally, teachers should be willing and able to change their mindset, they are old and will soon retire. Teachers must be willing to be open to changing times because teachers are real lifelong learners. Teachers are role models and agents of life change. Keywords: Globalization, Teacher, Volatality, Uncertainty, Complexity, Ambiguity